Complete and Partial Tears of the Anterior Cruciate Ligament: Acute and Evolution - Khaled, Wassef; Gerometta, Antoine; Guerini, Henri; Monzani, Quentin; Pessis, Eric; Campagna, Raphaël; Bouvier, Fadila Mihoubi; Drapé, Jean-Luc; Feydy, Antoine (Seminars in Musculoskeletal Radiology, 2025)
Anterior cruciate ligament tears represent a prevalent injury in sports that involves rotational movements and rapid changes in direction, such as pivot-contact sports. The anterior cruciate ligament serves as the primary stabilizer of the knee, preventing anterior tibial translation and medial tibial rotation. Although clinical examination is essential for diagnosis, magnetic resonance imaging plays a crucial role in confirming complete tears and evaluating associated injuries, particularly meniscal injuries. Diagnosis relies on both direct and secondary signs that are instrumental in assessing knee laxity and stability. Despite advancements in imaging techniques, challenges persist in using magnetic resonance imaging to distinguish between complete and partial tears, evaluate knee instability, and determine the potential for anterior cruciate ligament healing.
Keywords: anterior cruciate ligament; magnetic resonance imaging; instability; tear